2020
DOI: 10.1038/s41477-020-0680-9
|View full text |Cite
|
Sign up to set email alerts
|

Syndromes of production in intercropping impact yield gains

Abstract: This publication is made publicly available in the institutional repository of Wageningen University and Research, under the terms of article 25fa of the Dutch Copyright Act, also known as the Amendment Taverne. This has been done with explicit consent by the author.Article 25fa states that the author of a short scientific work funded either wholly or partially by Dutch public funds is entitled to make that work publicly available for no consideration following a reasonable period of time after the work was fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
270
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 392 publications
(298 citation statements)
references
References 63 publications
24
270
2
2
Order By: Relevance
“…They were 26.57, 29.39 and 32.68 for the corresponding treatments in the 2 nd season. These results are in agreement with those obtained by Li et al (2020) whom revealed that both the low-and high-yield intercropping strategies saved 16-29% of the land and 19-36% of the fertilizer compared with monocultures grown under the same management as the intercrop. Also, they found that the land savings in intercrops with maize were 13% larger than in intercrops without maize.…”
Section: Intercropping Efficiencysupporting
confidence: 92%
“…They were 26.57, 29.39 and 32.68 for the corresponding treatments in the 2 nd season. These results are in agreement with those obtained by Li et al (2020) whom revealed that both the low-and high-yield intercropping strategies saved 16-29% of the land and 19-36% of the fertilizer compared with monocultures grown under the same management as the intercrop. Also, they found that the land savings in intercrops with maize were 13% larger than in intercrops without maize.…”
Section: Intercropping Efficiencysupporting
confidence: 92%
“…Any complementarity that exists in an intercropping combination can enhance another complementarity by improving plant performance as the plant functions as an integrated whole. It is therefore totally expected that, if plant growth is enhanced in intercropping due to competitive relaxation for one or more resources (Li et al 2020a), resource acquisition will be enhanced for multiple resources as a result of such feedback, with little chance to identify which resource complementarities were the original drivers and which were the consequence. As a matter of fact, the complementarity that is a driver at one phase of crop growth may be a consequence during another phase.…”
Section: Does Improved P Uptake Intercrops Cause Yield Increase?mentioning
confidence: 99%
“…Global agriculture is facing the need to maintain crop yields, but with lower synthetic fertilizer inputs and higher environmental safety (Tilman, Balzer, Hill, & Befort, 2011). Ecological intensification by intercropping with different varieties or different species is one way to achieve these goals (Bender, Wagg, & van der Heijden, 2016; Bommarco, Kleijn, & Potts, 2013; Li et al., 2020). Our data show that mixing maize varieties could be a promising strategy to enhance P fertilizer acquisition efficiency.…”
Section: Discussionmentioning
confidence: 99%